Komparasi Penggunaan e-wallet Menggunakan Technology Acceptance Model (TAM) - Varlan, Paulina Enjelika (JATISI, 2024)
The world has witnessed how rapid advances in information and communication technology can change human life and the global economic order. One of the latest technological advances is the payment system using e-wallets. This study aims to determine how the comparison of user satisfaction of Dana and Ovo e-wallets in generation Z. The procedure in this study uses questionnaires as data collection using a Likert scale, the population in this study is generation Z in Malang City who use e-wallets and have met the criteria that have been determined in the study. This study uses the TAM method in order to compare the variables of perceived ease of use, perceived usefulness, attitude towards using the e-wallet application in Generation Z. The results showed that generation Z is more likely to use e-wallet applications in Generation Z. The results showed that generation Z chose Dana's e-wallet more than Ovo with 55 respondents and 45 respondents. But from the test results, Ovo has more influence on user satisfaction in terms of perceived benefits compared to Dana.